The Effect of Distance From Injection Site to the Brainstem Using Spinal Sufentanil. Issue 4 (1st July 2001) - Swenson, Jeffrey D.; Owen, John; Lamoreaux, Wayne; Viscomi, Christopher; McJames, Scott; Cluff, Mark
Abstract : Background and Objectives: Intrathecal (IT) sufentanil is commonly used in parturients to provide rapid onset of labor analgesia without motor block. This practice, although widely used, has been associated with severe respiratory depression in some patients. The mechanism of this respiratory depression is unclear, however, rapid cephalad movement and interaction with parenteral opioids are 2 frequently cited explanations for this complication. Because this complication has occurred only in women with heights between 150 and 157 cm, we elected to study the effect of the distance from injection site to the cisterna magna (CM) on peak brainstem cerebrospinal fluid (CSF) concentrations. Methods: Ten adult ewes were injected with IT sufentanil (0.3 μg/kg) at a mean distance of either 71 cm (65 to 78 cm) from the brainstem (pelvic group) or 37 cm (34 to 42 cm) from the brainstem (thoracic group). CSF was then sampled at 5-minute intervals from the CM. Results: Measurable CM concentrations of sufentanil were noted in the brainstem at 20 and 25 minutes, respectively, for the thoracic and the pelvic groups. Peak sufentanil concentrations from the thoracic group were nearly 10-fold higher (0.553 ± 0.43 ng/mL) compared with the pelvic group (0.064 ± 0.002 ng/mL) when measured in the CM ( P = .023). Conclusions: Our results suggest that sufentanil migrates relatively large distances in the IT space. Injection site (distance from the brainstem) appears to be a prominent factor in determining brainstem concentrations and subsequent respiratory depression after spinal administration.